Organic Certification Procedures and Costs - James J. Ferguson (EDIS)
Production and handling operations applying for initial or ongoing organic certification must comply with regulations established under the National Organic Program (NOP) and applicable organic production and handling regulations. The purpose of this document is to present information about organic certification procedures and estimated certification costs. This document is HS971, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2004.